(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article is an important overview of scientific research and education on the issues of the application of innovative technologies in the context of the digital economy. The article highlights the beneficial aspects of increasing the growth processes of the digital economy, establishing innovation, and applying innovative technologies to the economy, highlighting the changes that have been brought to the economy. For specialists in the field of digital economics, innovators, and scientific researchers, it is recommended to read the article, since this article explains the innovations of the digital economy and the tasks of its application.